A course on gender and cost-benefit analysis of innovations to enhance smallholder farmers' adaptation to climate change - Kramer, Berber; Braun, Mélody; Smith Ruiz, Paulina; Taheri, Homa (2024)
With support from the CGIAR Gender Impact Platform, AICCRA offered an online course on integrating gender in cost-benefit analysis of resilience intervention. This course was delivered for the first time spread across five sessions over the course of four weeks, from November 11th to December 6th, 2024. The course covered gender aspects of evaluating an intervention using net present value, an expected utility framework to quantify welfare gains from reduced risk, changes in women’s workloads and empowerment, as well as experimental and quasi-experimental impact evaluation methods. This course was part of the training courses of the CGIAR Gender Impact Platform for researchers, students, development practitioners and others looking to boost their knowledge and skills on gender in food systems. The aim of this course was to guide and strengthen agricultural research-for-development, ensuring it has meaningful and lasting contributions to global targets for gender equality, opportunities for youth and social inclusion.